Synthesis, Thermal Adsorption, and Energy Storage Calibration of Polysulfone Nanocomposite Developed with GNP/CNT Nanofillers - L. Prabhu; R. Saravanan; A. Anderson; A. Senthilkumar; V. N. Aneesh; Avinash Malladi; A. Mohana Krishnan; Manaye Majora (Adsorption Science & Technology)
The growth of polymer-based materials is becoming requisite in various industrial applications like energy storage, automobile, membrane, and orthopaedics, due to advantages over conventional metallic metal, such as less weight, superior corrosion resistance, ease of the process, and good chemical stability. The current research work is to synthesize the polysulfone (PSU) nanocomposite consisting of 2 wt%, 4 wt%, and 6 wt% of graphene nanoplatelets (GNP) and 3 wt%, 5 wt%, and 7 wt% of carbon nanotube (CNT) nanofillers via cast solution technique. The synthesized composite microstructural, heat storage, and thermal adsorption characteristics are studied. The scanning electron microscopic examination for both PSU/GNP and PSU/CNT composites illustrates good interfacial bonded PSU structure with the uniform distribution of GNP and CNT nanofillers. Due to the effect of percolation, the thermal adsorption characteristics and heat storage of PSU nanocomposite were increased progressively with the additions of GNP/CNT. The PSU composite contained 6 wt% GNP and 7 wt% CNT nanofillers, which showed effective thermal conductivity of 1.23 W/m.K and 1.52 W/m.K, which is 1.7 times larger than the unreinforced polysulfone. Interestingly, the increased temperature of the glass transition decreased the thermal expansion of the nanocomposite.